Physico-Microbial Properties of Cervico-Vaginal Mucus and its Antibiotic Sensitivity Pattern in Repeat Breeding Buffaloes - SHARMA, SHIV KUMAR; SHARMA, HITENDRA; DHAMI, A J; BHONG, C D (The Indian Journal of Animal Reproduction, 2023)
Forty five cervico-vaginal mucus samples from repeat breeding buffaloes on examination revealed clear thin watery, clear stringy and turbid consistency of mucus in 55.55, 33.33 and 11.11 % cases, respectively; while as in IO normal cyclic animals, 70.00 and 30.00 % samples were clear stringy and clear thin watery, respectively. Typical, atypical and nil fern pattern of oestrual mucus was observed in 33.33, 60.00 and 6.66 % samples of repeat breeders, and in 80, 20 and 0.00 % of normal cyclic buffaloes, respectively. Maximum number of normal cyclic and repeat breeding buffaloes conceived when they had clear stringy mucus (85.72 and 60.00 %), followed by those with clear thin watery mucus (33.33 and 20.00 %) and those with typical fern pattern (87 .50 and 46.66 %), but none with turbid mi.Jc us and nil fern pattern. The spinnbarkeit value of mucus from repeat breeding and normal cyclic buffaloes was ide.ntical (9.76 ± 0.56 and I 0.30 ± 0.93 cm), but those conceived had significantly higher (P <; 0.0 I) spinnbarkeit value as compared to those that did not conceive (12.5 vs 8.2 cm). Of the total 37 mucus samples of repeating buffaloes cultured,.35 (94.60 %) were positive for microorganisms; while from 10 normal breeding buffaloes only 2 (20.00 %) yielded microorganisms. Out of 35 positive samples from repeating buffaloes, 31(88.57 %) had single (12 gram +ve, 19 gram -ve) and 4 (11.43 %) had mixed bacterial isolates. Single isolates were more susceptible to the entire range of drugs tested, viz., ciprofloxacin (91.42 %), cephalexin (85.71 %), gentamicin (85.71 %), ceftriaxone (82.86 %), ampicillin (82.86 %), enrofloxacin (80.00 %) and oxytetracycline (77.14 %), while as ,mixed isolates showed highest resistance to these antibiotics. Cephalexin 4 gm and ceftriaxone 2 gm used as post-Al intrauterine infusion in 6 cases each was highly effective as 8 (66.66 %) animals cqnceived within 2 cycles.